2014
DOI: 10.1097/fpc.0000000000000087
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in AREG and EREG are prognostic biomarkers in locally advanced gastric cancer patients after surgery with curative intent

Abstract: Objective Amphiregulin (AREG) and epiregulin (EREG) are important ligands to the epithelial growth factor receptor (EGFR) which is involved in the regulation of progression and stemness in gastric cancer (GC). This study investigated whether frequent single nucleotide polymorphisms (SNPs) in genes of AREG and EREG are associated with recurrence-free survival and overall survival in patients with locally advanced gastric cancer (GC). Methods SNPs with a minor allele frequency of ≥10% were analyzed using direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Numerous studies have shown that high YAP and TAZ expression possess higher proliferative capability through transcriptional regulation of genes associated with cell cycle and division 45–47 . Except for YAP/TAZ, upregulation of their target genes, including CTGF, Cyr61, and AREG, has also been shown to promote tumorigenesis in gastric cancer 48–50 . MST1 inhibits YAP activation and acts as a tumor suppressor 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that high YAP and TAZ expression possess higher proliferative capability through transcriptional regulation of genes associated with cell cycle and division 45–47 . Except for YAP/TAZ, upregulation of their target genes, including CTGF, Cyr61, and AREG, has also been shown to promote tumorigenesis in gastric cancer 48–50 . MST1 inhibits YAP activation and acts as a tumor suppressor 12 .…”
Section: Discussionmentioning
confidence: 99%
“… 45 , 46 , 47 Except for YAP/TAZ, upregulation of their target genes, including CTGF, Cyr61, and AREG, has also been shown to promote tumorigenesis in gastric cancer. 48 , 49 , 50 MST1 inhibits YAP activation and acts as a tumor suppressor. 12 Genetic knockout MST1 results in hyperactivation of YAP and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous experiments have concentrated on the association between EREG SNPs and various diseases. Takeru Wakatsukiet al [24] identified SNPs within the genomic regions of EREG in gastric cancer for the first time and demonstrated an association of those SNPs with the 3-year RFS (recurrence free) and 3-year overall survival rates. In a study of Behçet’s disease (BD) with a case-control study of 976 Iranian patients and 839 healthy controls, a new SNP, rs6845297, located downstream of EREG , was associated with BD [25].…”
Section: Discussionmentioning
confidence: 99%
“…41 Interestingly, MTORC2 activity was not detected in primary human and mouse CRC samples, but was found to be expressed in macrophages where it contributed to antitumor activity. 42 A number of factors other than KRAS/NRAS and BRAF mutations influence the efficacy of anti-EGFR therapy, including plasma levels of EGFR ligands such as amphiregulin (AREG) and epiregulin (EREG), 43 and these may be monitored to provide an indication of resistance to anti-EGFR therapy. 24 EGFR gene copy number and acquired mutations in extracellular domains also may contribute anti-EGFR therapy resistance in mCRC.…”
Section: Current Biomarker-based Stratification Of Mcrcmentioning
confidence: 99%